The use of botulinum toxin type A in the treatment of spasticity of the lower limbs in stroke patients. Clinical case - A. P. Kovalenko (Нервно-мышечные болезни)
The article describes a clinical case of spasticity and its treatment with botulinum toxin type A in a patient with the consequences of acute stroke. Given a comprehensive assessment of patterns of spasticity and muscle involved in the syndrome. Described in detail and the result is the introduction of a technique. It is concluded that the effectiveness and feasibility of using Botox to treat spasticity of the lower limb.